2000
DOI: 10.1073/pnas.160249097
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of caveolin-3 in skeletal muscle fibers induces a Duchenne-like muscular dystrophy phenotype

Abstract: It recently was reported that Duchenne muscular dystrophy (DMD) patients and mdx mice have elevated levels of caveolin-3 expression in their skeletal muscle. However, it remains unknown whether increased caveolin-3 levels in DMD patients contribute to the pathogenesis of DMD. Here, using a genetic approach, we test this hypothesis directly by overexpressing wild-type caveolin-3 as a transgene in mice. Analysis of skeletal muscle tissue from caveolin-3-overexpressing transgenic mice reveals: (i) a dramatic incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
91
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 46 publications
(45 reference statements)
13
91
2
Order By: Relevance
“…12 Conversely, transgenic over-expression of Cav-3 in skeletal muscle fibers induces a Duchenne-like muscular dystrophy phenotype, and causes the down-regulation of dystrophin and of dystrophin-associated proteins. 39 Taken together, these results suggest that a particular ratio between Cav-3 and dystrophin may be crucial for the proper functioning of skeletal muscle. Recent studies have attempted to gain insight in the molecular basis of these observations, and have demonstrated that Cav-3 directly interacts with ␤-dystroglycan, at the same or an overlapping site as dystrophin.…”
Section: Discussionmentioning
confidence: 80%
“…12 Conversely, transgenic over-expression of Cav-3 in skeletal muscle fibers induces a Duchenne-like muscular dystrophy phenotype, and causes the down-regulation of dystrophin and of dystrophin-associated proteins. 39 Taken together, these results suggest that a particular ratio between Cav-3 and dystrophin may be crucial for the proper functioning of skeletal muscle. Recent studies have attempted to gain insight in the molecular basis of these observations, and have demonstrated that Cav-3 directly interacts with ␤-dystroglycan, at the same or an overlapping site as dystrophin.…”
Section: Discussionmentioning
confidence: 80%
“…21 In addition, Cav-3 was shown to bind b-dystroglycan at a similar or overlapping site as dystrophin, thus indicating that Cav-3 and dystrophin may compete for the binding site to b-dystroglycan, and that Cav-3 expression levels may regulate the recruitment of dystrophin to the plasma membrane. 30 Thus, we tested whether MLN273 treatment would decrease abnormally elevated Cav-3 levels in mdx skeletal muscles, which maybe important for improvement of pathological signs.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Cav-3 is increased in skeletal muscle fibers from mdx mice and DMD patients, 9,10 whereas transgenic over-expression of Cav-3 in skeletal muscles induces a Duchenne-like phenotype. 21 As such, we assessed whether treatment with MLN273 would normalize Cav-3 expression levels. Figure 4 shows that treatment with all three concentrations (20 mM, 100 mM and 160 mM) of MLN273 induces Immunohistochemistry.…”
Section: Localized Treatment With the Proteasomal Inhibitor Mln273mentioning
confidence: 99%
“…Caveolin-1 and caveolin-2 are coexpressed in many cell types, including adipocytes, endothelial cells, epithelial cells, and fibroblasts (9). In contrast, caveolin-3 expression is essentially restricted to skeletal and smooth muscle cells, as well as cardiac myocytes (10)(11)(12)(13)(14)(15)(16)(17)(18). The direct interaction with caveolin-1 results in the inhibition of a number of signaling molecules, such as G-protein a subunit, Ras, nitric oxide synthase, protein kinase C, and protein kinase A (2,7,10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%